Lingkungan Positif yang Mendukung Pembelajaran - Habsy, Bakhrudin All; Wandari, Nadya Indria; Wulandari, Dewi Putri (Lembaga Yasin AlSys, 2024)
The purpose of this study is to comprehend the conducive atmosphere that facilitates learning. The study employed a library research methodology and a questionnaire using data sourced from multiple online resources, including books, encyclopedias, dictionaries, journals, documents, magazines, and other materials. A safe, encouraging, and learning-focused learning atmosphere is what makes kids feel good about their education. A supportive learning environment can not only help students grow emotionally but also make a big difference in their academic performance. Students will be able to process, learn, make errors, and learn again in a safe and comfortable setting, which will help them to effectively receive and assimilate information. An environment that is conducive to learning might be physical, emotional, and as well as sociological elements. There are many strategies to create a positive learning environment, including making the material relevant, coming up with an ethical code, rewarding good behavior, offering emotional support, setting up routines and structures, furnishing the classroom with comfortable furniture, and so on. Enhancing the learning environment can help students feel more at ease and driven to learn, which will lead to better learning results.